2017
DOI: 10.1093/bmb/ldx036
|View full text |Cite
|
Sign up to set email alerts
|

Who bears the cost of NICE public health recommendations?

Abstract: Future NICE guidance should report disaggregated costs across the sectors where they fall. Further research is needed to conceptualize the opportunity cost of financial burdens falling on non-health budgets before optimal decision making in public health is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, previous research has shown that health care costs are the predominant category of cost impact within NICE public health guidance. 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous research has shown that health care costs are the predominant category of cost impact within NICE public health guidance. 25…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown that health care costs are the predominant category of cost impact within NICE public health guidance. 25 Previously, Owen et al 13,26 examined the costeffectiveness of public health interventions underpinning NICE public health guidance. Our study is the first to examine the health inequality impacts of those same interventions and follows the same principles outlined for full distributional cost-effectiveness analysis.…”
Section: Discussionmentioning
confidence: 99%